2023
DOI: 10.21203/rs.3.rs-2750656/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Functionality Appreciation Scale (FAS): psychometric properties and results of the Dutch version in a community sample and a sample of women with eating disorders

Abstract: Background Body satisfaction in people with eating disorders (EDs) is negatively affected by their critical evaluation of aesthetic aspects. A focus on body functionality could create a more positive perspective. This study examines psychometric properties of the Dutch version of the Functionality Appreciation Scale (FAS) and differences in scores between women with and without EDs. Method Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were used to investigate the factor structure in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…In addition, the factorial validity of the FAS has also been assessed in a wide range of national and linguistic contexts. Thus, the 7-item, unidimensional model of FAS scores has been supported in samples of adults from Brazil (in Brazilian Portuguese; Faria et al, 2020), Cyprus (in Greek; Anastasiades et al, 2023), Italy (in Italian; Cerea et al, 2021), Japan (in Japanese; Namatame et al, 2022), Lebanon (in Arabic; Swami et al, 2022), Malaysia (in Malaysian Malay; , the Netherlands (in Dutch; Rekkers et al, 2023), and Romania (in Romanian; , a sample of different age groups (adolescents to older adults) in China (in Chinese; He et al, 2022; see also Wang et al, 2022), as well as adolescents from the United Kingdom (in English; Todd et al, 2019) and Iran (in Persian; Sahlan et al, 2022). One study has also demonstrated that the FAS is partially invariant across adults in two national contexts (i.e., Malaysia and the United Kingdom; Todd & Swami, 2020), suggesting at least preliminarily that the FAS may be suitable for use in cross-cultural research.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, the factorial validity of the FAS has also been assessed in a wide range of national and linguistic contexts. Thus, the 7-item, unidimensional model of FAS scores has been supported in samples of adults from Brazil (in Brazilian Portuguese; Faria et al, 2020), Cyprus (in Greek; Anastasiades et al, 2023), Italy (in Italian; Cerea et al, 2021), Japan (in Japanese; Namatame et al, 2022), Lebanon (in Arabic; Swami et al, 2022), Malaysia (in Malaysian Malay; , the Netherlands (in Dutch; Rekkers et al, 2023), and Romania (in Romanian; , a sample of different age groups (adolescents to older adults) in China (in Chinese; He et al, 2022; see also Wang et al, 2022), as well as adolescents from the United Kingdom (in English; Todd et al, 2019) and Iran (in Persian; Sahlan et al, 2022). One study has also demonstrated that the FAS is partially invariant across adults in two national contexts (i.e., Malaysia and the United Kingdom; Todd & Swami, 2020), suggesting at least preliminarily that the FAS may be suitable for use in cross-cultural research.…”
Section: Introductionmentioning
confidence: 93%